原式乘以(3-1)再除以2
原式=(3^64-1)/2=1716841910146256242328924544640
(3+1)(3^2+1)(3^4+1)(3^8+1)(3^16+1)(3^32+1)
=(3-1)(3+1)(3^2+1)(3^4+1)(3^8+1)(3^16+1)(3^32+1)÷2
=(3^2-1)(3^2+1)(3^4+1)(3^8+1)(3^16+1)(3^32+1)÷2
=(3^4-1)(3^4+1)(3^8+1)(3^16+1)(3^32+1)÷2
=(3^8-1)(3^8+1)(3^16+1)(3^32+1)÷2
=(3^16-1)(3^16+1)(3^32+1)÷2
=(3^32-1)(3^32+1)÷2
=(3^64-1)/2
(3-1)(3+1)(3^2+1)(3^4+1)(3^8+1)(3^16+1)(3^32+1)/(3-1)
=(3^2-1)(3^2+1)(3^4+1)(3^8+1)(3^16+1)(3^32+1)/2
=(3^4-1)(3^4+1)(3^8+1)(3^16+1)(3^32+1)/2
……
=(3^64-1)/2
(3-1)*...
(3^64-1)/2
(3+1)(3^2+1)(3^4+1)(3^8+1)(3^16+1)(3^32+1)
=(3-1)(3+1)(3^2+1)(3^4+1)(3^8+1)(3^16+1)(3^32+1)/2
=(3^2-1)(3^2+1)(3^4+1)(3^8+1)(3^16+1)(3^32+1)/2
=……
=(3^64-1)/2